KORELASI FAMILY EMPOWERMENT DENGAN SELF-MANAGEMENT PADA PENDERITA DIABETES MELITUS TIPE II DI KABUPATEN TULUNGAGUNG: Correlation Of Family Empowerment with Self-Management in Patients With Type II Diabetes Mellitus In Tulungagung District - Nizar, Angga Miftakhul; Dwi Prasetio, Ossi; Arief Hidayat, Shulhan; Intan Munawaroh (Jurnal Penelitian, 2024)
Diabetes mellitus is a chronic disease that cannot be cured and requires lifelong treatment, therefore assistance or support from the family will help clients in improving diabetes mellitus control management. This research aims to determine the correlation between family empowerment and Self-Management in patients with a history of type II diabetes mellitus in Tulungagung Regency. This research was quantitative research with a cross-sectional survey method. The research instrument used the Family Empowerment Scale (FES) and The Diabetes Self-Management (DSMQ) questionnaire to determine self-management. The sampling method was carried out using a purposive technique, resulting in a sample size of 320 respondents. The independent variable was family empowerment (X) while the dependent variable was Self-Management (Y). Based on the Spearman rho test results, the ρ value = 0.000 < 0.05, meaning that there was a relationship between family empowerment and Self-Management in patients with a history of type II diabetes mellitus in Tulungagung Regency. With a correlation coefficient value of r = 0.7, it can be concluded that the strength of the relationship is strong. The direction of the relationship is linear (+), which means that the better the level of family empowerment obtained by DM sufferers, the better the level of Self-Management possessed by the respondent. Based on these results, can be used as consideration for related parties to improve the Self-Management of DM sufferers through providing family empowerment.   Keywords: Diabetes Mellitus; Family-Empowerment; Self-Management